Anniversary of Petras Zalanskas and Dzūkija Culture Festival “Čiulba ulba” - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2020)
This year we celebrate 120 years anniversary of the famous folk singer from Dzūkija region and an original folklore interpreter Petras Zalanskas (1900–1980), who lived and died in Mardasavas village (Varėna district). Although Zalanskas has passed away four decades ago, his songs still frequently sound performed by other singers at various musical events. The article surveys one such event taking place this year – namely, the Dzūkija culture festival “Čiulba ulba”, which was the biggest and longest celebratory “commotion”. This festival is going to be an annual one that would be dedicated to various prominent personalities every year, linking together many things that are related to Dzūkija region: a film about partisans from Dzūkija, poetry in local dialect, music, crafts, and dialect. The first such festival took place in Zalanskas’ native village of Mardasavas on September 4–6, 2020. It was also a festival of local folksongs, attracting a big number of singers. The main organizer Eglė Kašėtienė made interviews with the participants and recorded their thoughts. The responses surveyed in the article highlight the individual attitudes of the folk singers and poets to Dzūkija and Zalanskas. Besides, they present a certain sectional view of the current folksong tradition. The young singers already represent the second or third generation reflecting upon the folksong legacy of Zalanskas. Having encountered the famous predecessor only in the archived recordings and books, they use their imagination and creativity to reinvigorate the “myth of Zalanskas”.